Malaysian Listed Firm’s Tax Avoidance: Another Earnings Management Strategy? - Mohd Waliuddin, Mohd Razali; Pong, Xiang Yi; Brahmana, Rayenda Khresna (Asian Academy of Management, 2015)
This study examines the role of tax avoidance on firm’s earnings management for a sample of 149 listed public firms in Malaysia over 2009 – 2013. Beneish M-score is used to measure the earnings management and effective tax rate to measure the tax avoidance. After controlling firm size, growth, leverage and profitability, the result shows that only two variables which tax avoidance and growth are positively significant towards the earnings management. The result implies that firms may manage their earning to enjoy tax advantages. Moreover, management in growth firms’ tent engages better earning performance and thus it may affect the firm investment strategies.